PENINGKATAN KOMPETENSI GURU SD DALAM MERANCANG PEMBELAJARAN BERDIFERENSIASI MELALUI KOMUNITAS BELAJAR DI KECAMATAN TANANTOVEA - Herlina Herlina; Ratman Ratman; Nasrullah Nasrullah; Yusdin Gagaramusu; Ammar Abdullah Joni Guci; Danti Indriastuti Purnamasari (Universitas Mataram, 2025)
This community service activity is motivated by the importance of improving elementary school teachers' competencies in designing differentiated learning, given the challenges faced in meeting the diverse needs of students. In Tanantovea District, many teachers do not fully understand the concept and application of effective differentiated learning. The purpose of this activity is to improve teachers' skills in designing and implementing differentiated learning through a learning community approach. Research focused on quantitative aspects aims to provide a systematic and factual overview of the factors, characteristics, and relationships between phenomena. Qualitative research is viewed as a process of exploring and strengthening predictions about phenomena based on field data. Following this activity, there was a significant increase in teachers' understanding and skills in designing differentiated learning. Teachers demonstrated improved skills in adapting teaching materials to the diverse needs of students in differentiated lesson plans using word walls. Furthermore, the former learning community strengthened collaboration among teachers and enabled them to share experiences and solutions to challenges. Post-test results indicated an increase in teachers' practical abilities in implementing more interactive and relevant differentiated learning techniques. This activity successfully improved elementary school teachers' competency in designing differentiated learning through a learning community approach, which has proven effective in supporting teacher professional development.